(untitled) (Journal of the College of Basic Education, 2023)
The audience is the main goal of any media outlet that intends to send a specific communication message. The primary goal of the media is to gain the largest number of recipients, whether with the intention of achieving its main functions, which are (media with the intent to inform, educate, entertain or advertise) as media .. or with the intention of influencing them. And just as the media has its goals towards the public, the audience also has its goals, which are represented by its needs first, which turn into motives that move it to a certain behavior in an effort to satisfy it through all media or a specific media that satisfies its needs, or through other means such as visits, going to certain places, or exercising. Specific actions, in pursuit of satisfying needs.Hence, the media began, each according to its techniques and capabilities, to seek the needs of the masses in order to satisfy them and gain their confidence in them. However, the multiplicity of media outlets at the present time, the multiplicity of needs of the masses, and the inability of the media to include a variety of media contents to provide news extensively made the means make a greater effort to win the largest number of recipients of their communication messages, and from here specialization appeared in the media, especially after electronic journalism. Which exceeded geographical boundaries and made the recipient in the farthest part of the world able to receive its communication messages.